2009
DOI: 10.1089/ten.tec.2008.0347
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Measurements of Hydrogel Tissue Construct Mechanics

Abstract: Engineered tissues represent a natural environment for studying cell physiology, mechanics, and function. Cellular interactions with the extracellular matrix proteins are important determinants of cell physiology and tissue mechanics. Dysregulation of these parameters can result in diseases such as cardiac fibrosis and atherosclerosis. In this report we present a novel system to produce hydrogel tissue constructs (HTCs) and to characterize their mechanical properties. HTCs are grown in custom chambers and a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…In literature, the reported active and passive cellular contributions to generated force are much higher. The active cellular contribution to force of fibroblasts in collagen gels was 35-65% (Marquez et al 2009;Youssef et al 2011;John et al 2010;Legant et al 2009) and lysation caused an additional 30% reduction of force below the level observed with CytoD treatment (Wakatsuki et al 2000). To measure a decrease in force within our model system, bending of the leaf springs must become less and this requires elongation of the TE constructs.…”
Section: Passive and Active Components In Force Generationmentioning
confidence: 94%
See 1 more Smart Citation
“…In literature, the reported active and passive cellular contributions to generated force are much higher. The active cellular contribution to force of fibroblasts in collagen gels was 35-65% (Marquez et al 2009;Youssef et al 2011;John et al 2010;Legant et al 2009) and lysation caused an additional 30% reduction of force below the level observed with CytoD treatment (Wakatsuki et al 2000). To measure a decrease in force within our model system, bending of the leaf springs must become less and this requires elongation of the TE constructs.…”
Section: Passive and Active Components In Force Generationmentioning
confidence: 94%
“…Active and passive phenomena have been investigated thoroughly in short-term studies with fibroblast-populated collagen and fibrin gel systems Marquez et al 2009;John et al 2010;Youssef et al 2011;Tomasek et al 1992;Grouf et al 2007;Balestrini and Billiar 2009). In tissue engineered heart valves, the ECM is developed during 4 weeks of tissue culture and is more mature than the generally investigated collagen and fibrin gels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the classical Langendorf preparation of an excised heart undergoes a significant deterioration of function over a few hours [27]. In contrast, cardiac tissue constructs preserve stable contractile function over many days [28]. (7) Applicability to screening.…”
Section: Engineered Tissue Constructsmentioning
confidence: 99%
“…However, in these micro-scale tissues, it is yet to be determined if there is an improvement of the statistical significance of functional data over that from single cells. At present, ETs in millimeter scale have been used for the functional assays with relatively good data reproducibility [8] [9]. By using ETs, a statistically significant data can be obtained using only 4-8 samples [9] instead of collecting ranging 60-600 data points per well in cell-based assays [10].…”
Section: Miniaturizing Biological Samples and Productsmentioning
confidence: 99%
“…At present, ETs in millimeter scale have been used for the functional assays with relatively good data reproducibility [8] [9]. By using ETs, a statistically significant data can be obtained using only 4-8 samples [9] instead of collecting ranging 60-600 data points per well in cell-based assays [10]. Unlike the rapid prototyping of parts with synthetic materials, the prototyping of engineered tissues with live cells has to consider the behavior of tissues after fabrication in a given culture condition.…”
Section: Miniaturizing Biological Samples and Productsmentioning
confidence: 99%